Adverse Events from Emollient Use in Eczema: A Restricted Review of Published Data - Alisha Bhanot; Alyson Huntley; Matthew J. Ridd (Adis, Springer Healthcare, 2019)
Abstract Atopic dermatitis/eczema is a chronic inflammatory skin condition, and emollients are the first-line treatment. Despite their widespread use, there is uncertainty about the frequency and type of adverse events associated with different emollients. We conducted a restricted review of published data on adverse events associated with emollient use in eczema. Medline (Ovid) was searched from inception (1946) to June 2018. All types of studies, with the exception of reviews, were included. Eligibility was assessed using a two-stage screening process against inclusion and exclusion criteria. References of all included papers were screened for any additional eligible papers. Data were subsequently extracted from all eligible publications. A limited body of data were found in the published data: 24 papers reported on adverse events with 29 different emollients (3 containing urea, 5 containing ceramide, 4 containing glycerol, 4 were herbal and 13 contained "other" ingredients). Interpretation of the results and comparison of the emollients were difficult due to poor reporting and missing data. Many publications contained no data at all on adverse events, and no study reported serious treatment-related adverse events for any emollient. The proportion of participants in the studies experiencing treatment-related adverse events varied between 2 and 59%. The most common adverse events were skin related and often mild. The range of participants experiencing non-treatment-related adverse events varied between 4 and 43%. From this restricted review, clinicians and patients can be reassured that the emollients studied appear to be generally safe to use. Better studies and reporting of adverse events associated with emollients in common use are needed.